ESTABLISHING KILN DRYING SCHEDULE FOR POPLAR (P. ALBA) LUMBER OF 7 CM IN THICKNESS - Hadi Dashti; Mohammad Ali Hossein; Mahdi Shahverdi (BioResources, 2011)
Poplar (Populus alba L.) lumber with a nominal thickness of 7 cm from the Taleghan region in Iran was dried through convective kiln drying and under three different programs of T5–D2 (Forest Product Laboratory proposed program for poplar), T5–D4, and T5–D6 in order to obtain the optimum kiln schedule so as to protect the wood quality at an appropriate level up to final moisture content of 12±2%. Subsequently, the intensities of warps, superficial and internal cracks occurrence, residual stresses, drying rate, and final moisture gradient were measured. Results revealed that due to low warping values, more homogeneous final moisture profile, fewer internal cracks, and absence of superficial cracks in the program T5–D2 compared to the other two (T5–D4 and T5–D6), this program can be recommended as an optimum program for poplar lumber drying at commercial scale from the Taleghan region. On the other hand and from an energy efficiency point of view, in comparison with the mild schedule (T5-D2), the severe schedule (T5-D6) by saving 456 h of drying time, reduced electricity consumption by 6156 KWh and was therefore found to be $ 240.08 more profitable in this trial.